A novel identifier scheme for the ISEA Aperture 3 Hexagon Discrete Global Grid System - Mocnik, Franz-Benjamin (Cartography and geographic information science, 2018)
Geospatial data is often spatially aggregated by the use of Discrete Global Grid Systems. References to grid cells are needed for the communication of such data, and different identifier schemes have accordingly been introduced in literature. These schemes suffer, however, from being hard to understand for non-experts, and the geometry of a cell cannot be inferred from its identifier without complex computations. In this article, a novel identifier scheme that encodes the geographic coordinates of the centroid of a cell is proposed, which comes at the cost of potentially being ambiguous in case of a very fine-grained grid. We reason and computationally demonstrate that ambiguity does though not occur for real-world applications. The novel identifier scheme minimizes the amount of data to be communicated, for example, between a server and a client application, and it allows to infer approximate geometries of the cells only by their identifiers.
Gesehen am 26.03.2019